Penyelesaian Kasus Jarimah Ikhtilat Di Gayo Menurut Hukum Islam - Jamhir Jamhir (Jurnal Justisia : Jurnal Ilmu Hukum, Perundang-undangan dan Pranata Sosial, 2020)
This research discusses "The settlement of the Jarimah Ikhtilat case in Gayo according to Islamic law". The formulation of the problem put forward is (1). How is the settlement of Jarimah ikhtilath according to Gayo customary law? (2) How is the settlement of Jarimah ikhtilath in Gayo according to Islamic law? This research is descriptive analysis. Using a qualitative approach, namely research describing the results of objective research on situations encountered in the field and analyzed according to Islamic law. The conclusion of this study shows that the customary legal sanctions given to ikhtilath actors in Gayo are a fine of one complete goat or a fine on the agreement of the village sarak opat. If viewed according to Islamic law, that customary law sanctions do not contradict the concept of Islamic law. Because, in Islam it is stipulated that the perpetrator of ikhtilath is part of the finger of ta'zir, where the imposition of the sentence is fully handed over by the government, both in type and size, starting from the lightest punishment such as giving advice to the perpetrator, fines, lashing or exile up to the highest punishment, namely the perpetrator must be killed. The customary law sanctions regarding the ikhtilath case in Gayo include ta'zir sanctions, which type and size are determined by Sarak Opat, namely in the form of a fine of one goat.